BENEFITS OF INDONESIAN SAINTIFIC JAMU IN THE TREATMENT OF VARIOUS DISEASES: A REVIEW - Gondokesumo, Marisca Evalina; Muthmainnah, Anis Syabani (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
One of Indonesia's treasures is herbal medicine. Jamu comes from Sanskrit, namely from the word djamoe which stands for djampi and oesodo. Djampi means healing with medicinal herbs or prayers and mantra while oesodo means health, so it is concluded that medicinal herbs are beneficial for health. Jamu is an ancestral heritage of the Indonesian Nation that has been passed down from generation to generation has high advantages because it comes from cultural diversity, local wisdom, and high biodiversity. Empirical evidence shows that herbal medicine can maintain and improve public health. The government, through the Ministry of Health, issued a regulation on the Saintification of Jamu to provide scientific evidence regarding the efficacy and safety of herbal medicine through health service-based research. Scientific herbs approved by the National Herbal Saintification Commission are sourced from research that has been conducted by the Center for Research and Development of Medicinal Plants and Traditional Medicines (B2P2TOOT). Currently there are 12 scientific jamu concoctions, but in the future it will definitely increase. This literature review uses a narrative method of grouping similar research results according to the established journal criteria. Based on the results of the literature review that has been carried out, it can be concluded that 12 scientific jamu concoctions are safe and have health benefits.